2020
DOI: 10.14715/cmb/2020.66.6.9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Salvia miltiorrhiza and Radix astragali on the TGF-β/Smad/Wnt pathway and the pathological process of liver fibrosis in rats

Abstract: Traditional Chinese medicine has made some progress in the study of liver fibrosis, and provides valuable experience for clinical treatment of liver fibrosis. The aim of this study was to investigate the rationality of compatibility use of Salvia miltiorrhiza and Radix astragali on liver fibrosis in rats. For this purpose, the rat model of liver fibrosis was treated with single or different compatibilities of herbals extracts for 4 weeks. Saline and colchicine were set as a negative and positive control, respe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 34 publications
2
7
0
Order By: Relevance
“…Wnt and its downstream effectors regulate various processes during cancer progression (including tumorigenesis, tumor growth, cellular senescence, and cellular death), differentiation, and metastasis 32 . Some previous studies have reported that there is a cross talk between the Wnt/β‐catenin pathway and TGF‐β/SMAD pathway 33,34 . Interestingly, in the present work, we demonstrated that SMAD2 could positively regulate the expression of WNT1 in BCa cells, and circ_0002623 could regulate WNT1 expression via the miR‐1276/SMAD2 axis.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Wnt and its downstream effectors regulate various processes during cancer progression (including tumorigenesis, tumor growth, cellular senescence, and cellular death), differentiation, and metastasis 32 . Some previous studies have reported that there is a cross talk between the Wnt/β‐catenin pathway and TGF‐β/SMAD pathway 33,34 . Interestingly, in the present work, we demonstrated that SMAD2 could positively regulate the expression of WNT1 in BCa cells, and circ_0002623 could regulate WNT1 expression via the miR‐1276/SMAD2 axis.…”
Section: Discussionsupporting
confidence: 54%
“… 32 Some previous studies have reported that there is a cross talk between the Wnt/β‐catenin pathway and TGF‐β/SMAD pathway. 33 , 34 Interestingly, in the present work, we demonstrated that SMAD2 could positively regulate the expression of WNT1 in BCa cells, and circ_0002623 could regulate WNT1 expression via the miR‐1276/SMAD2 axis. However, the detailed mechanism by which SMAD2 regulates WNT1 is still obscure, which requires further investigation.…”
Section: Discussionsupporting
confidence: 47%
“…The combination of Astragalus and Salvia miltiorrhiza Bunge is also commonly used in fibrotic diseases. Studies have proven this combination has favorable therapeutic efficacy in hypertrophic scar ( Wu et al, 2014 ), liver fibrosis ( Cao et al, 2020 ), cardiac fibrosis ( Mao et al, 2015 ; Zhang et al, 2021b ), renal fibrosis ( Han et al, 2021 ).…”
Section: Effect Of Astragalus On Fibrotic Diseasesmentioning
confidence: 99%
“…In addition to the direct effects of inhibiting the activated HCSs, SM could indirectly enhance the activities of NK cell to reduce liver fibrosis ( Peng et al, 2018 ). Several experimental studies had reported that SM could couple with some herbal medicines, such as radix astragali ( Yang et al, 2008 ; Cao et al, 2020 ), stephania tetrandra ( Chor et al, 2009 ), ligusticum chuanxiong and glycyrrhiza glabra ( Lin et al, 2008 ), to exert the antifibrotic effects via alleviating collagen deposition and reducing inflammation in the liver. Moreover, the active anti-fibrotic ingredients from SM have gained an increasing amount of attention.…”
Section: Pharmacological Actions Of Salvia Miltiorrhiza ...mentioning
confidence: 99%